The results and prospects of maize breeding in the Agricultural Research Center “Donskoy” - G. Ya. Krivosheev; N. A. Shevchenko; A. S. Ignatiev (Зерновое хозяйство России)
The current paper has presented the results of breeding work on maize in the Agricultural Research Center “Donskoy”. The three-line and double interlinear middle early and middle ripening maize hybrids of various economic use ‘Zernogradsky 242 MV’, ‘Zernogradsky 282 MV’, ‘Zernogradsky 288 MV’, ‘Zernogradsky 299 MV’, ‘Zernogradsky 354 MV’, ‘Zernogradsky MV’, ‘Stepnyak MV’ were developed and included into the State List of Breeding Achievements from 2006 to 2020. The Competitive Variety Testing has identified a new high-heterosis simple hybrid ‘Zernogradsky 352 MB’ and the new early ripening hybrids ‘Krucha M × KB 215’, ‘Krucha M × SP 56/57’ with low harvesting grain moisture. The main method used to develop maize hybrids was an interline hybridization using heterosis in the first generation (F1 ). There have been determined the priority directions of further breeding, namely early ripeness, grain humidity-transfer intensity during ripening, drought resistance, high starch content in grain. There has been developed new initial material for each direction of breeding. There have been selected the introduced testers (‘Alpha M’, ‘Almaz M’, ‘Aurora S’, ‘Milena M’, ‘Istok S’) to develop early-ripening hybrids. There have been identified the early and middle-early ripening self-pollinated lines ‘C 207’, ‘RD 12’, ‘TVA 308’, ‘PLS 61’, ‘KB 215’, etc., with a high grain humidity-transfer intensity during ripening (0.95–1.30% per day), low harvest moisture content of grain (10.8–13.8%). There have been developed the new self-pollinated waxy maize lines (24/29/5, 25/64/10, 26/8, 26/4, 26/80, 24/28) with 68.1–69.8% of amylopectin starch in grain. There have been identified the new self-pollinated maize lines resistant to water stress (DS 498/217-3, DS 257/85-5, DS 498/203, KB 262, etc.) promising for breeding drought-resistant maize hybrids.